A Sunny Little Lass - Raymond, Evelyn, 1843-1910 (Salt Lake City, UT : Project Gutenberg, 2010)
"A Sunny Little Lass" by Evelyn Raymond is a novel written in the early 20th century. The story focuses on a little girl named Glory and her relationship with her blind grandfather, Captain Simon Beck, as they navigate life in a cramped, impoverished space in New York City. The book explores themes of love, resilience, and the harsh realities of urban life while depicting the innocence and imagination of a young girl who dreams of a better future. At the start of the novel, we are introduced to Glory and her grandfather living in (3z(Bthe littlest house in Ne' York.(3y (BTheir humble abode, filled with maritime charm, reflects their close bond and shared dreams of a brighter life at (3z(BSailors$1 (BSnug Harbor.(3y (BThe narrative showcases Glory$1 (Bs optimistic spirit as she handles everyday struggles with cheerfulness, while her grandfather's recent discontent raises concerns about their future. Their lives take a sudden turn when a wealthy stranger ominously suggests that they might need to separate, leaving Glory worried about losing her beloved grandpa forever. This opening sets the stage for a poignant tale of adventure as Glory embarks on a desperate search for her grandfather amid the bustling city. (This is an automatically generated summary.)s
Release date is 2010-01-15
E-text prepared by Roger Frank, D Alexander, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Orphans -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction; Grandfathers -- Juvenile fiction; Poor girls -- Juvenile fiction